1988
DOI: 10.1063/1.341487
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions of cobalt thin films on BF+2 ion-implanted (001) silicon

Abstract: Interfacial reactions of cobalt thin films on BF+2 -implanted (001)Si have been studied by both cross-sectional and plan-view transmission electron microscopy as well as by sheet resistance measurements. The implantation-amorphous samples were found to favor the formation of CoSi2 at 400 °C and laterally uniform growth of the phase at higher temperatures. Two discrete layers of fluorine bubbles were observed in cobalt silicides in all BF+2 -implanted samples annealed at 400–800 °C. In 800–900 °C annealed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, bubbles were found in the vicinity of the surface, presumably because of fluorine from the BF2 implantation. Fluorine bubble formation was previously observed at CoSt2 grain boundaries after the silicide was formed on BF2-implanted silicon (35). The same results were obtained for TiSi2, Fig.…”
Section: Resultssupporting
confidence: 86%
“…However, bubbles were found in the vicinity of the surface, presumably because of fluorine from the BF2 implantation. Fluorine bubble formation was previously observed at CoSt2 grain boundaries after the silicide was formed on BF2-implanted silicon (35). The same results were obtained for TiSi2, Fig.…”
Section: Resultssupporting
confidence: 86%
“…Increase of thermal stability of silicide layers on BF 2 + implanted silicon was reported also for CoSi 2 [7] and TiSi 2 [8]. The authors suggested a synergetic effect of B and F retarding the degradation of the silicide morphology.…”
Section: Discussionmentioning
confidence: 87%
“…Typically, the first cobalt silicide phase to form on silicon substrate is Co 2 Si (300-450 1C) followed by CoSi (350-500 1C) and subsequent CoSi 2 (X550 1C) formation [3,4]. In addition, the phase transformation of high-resistivity CoSi ($150 mO cm) to low-resistivity CoSi 2 was found to occur according to nucleation-controlled kinetics [5].…”
Section: Introductionmentioning
confidence: 97%